The Impact of Firm Size and Governance on Corporate Tax Avoidance Strategies - I Made Dwi Sumba Wirawan (Jurnal Riset Perpajakan: Amnesty, 2025)
This study investigates the impact of firm size and corporate governance on tax avoidance strategies in property and real estate companies listed on the Indonesia Stock Exchange (IDX) between 2020 and 2022. Tax avoidance, although legal, raises concerns about tax fairness, transparency, and state revenue sustainability. Using a quantitative approach with multiple linear regression analysis, the study examines the roles of firm size, board of directors, independent commissioners, and audit committees in influencing tax avoidance behavior. Data were collected from 58 companies, resulting in 174 firm-year observations. The findings reveal that firm size has a significant negative effect on tax avoidance, indicating that larger firms tend to avoid aggressive tax planning, possibly due to higher public scrutiny and reputational risks. In contrast, the board of directors, independent commissioners, and audit committees show no significant influence on tax avoidance practices. These results suggest that traditional corporate governance mechanisms may be insufficient in curbing tax avoidance in Indonesia’s property sector, highlighting the need for more targeted regulatory interventions and enhanced governance practices. This study contributes to the growing literature on corporate tax behavior in emerging markets by offering empirical evidence from the real estate industry, which is often characterized by asset intensity and unique regulatory treatment. The findings have practical implications for policymakers and regulators seeking to strengthen tax compliance through firm-level characteristics and governance reforms. Future research is encouraged to explore additional moderating variables such as profitability, leverage, and ownership structure to gain a more comprehensive understanding of corporate tax avoidance behavior in the Indonesian context.